Moderate and Tolerant Attitudes in the Perspective of Hadith: A Case Study of Tolerance towards Minorities in the Context of Contemporary Indonesia - Rizky Wahyu Satria; Endad Musaddad (Al-Hukumah: Jurnal Ilmu Pemerintahan dan Studi Islam, 2025)
This research analyzes the concept of moderate and tolerant attitudes from the perspective of Prophet Muhammad's hadith, focusing on their implementation toward minorities in contemporary Indonesia. Employing a qualitative approach through hadith textual analysis and case studies, this research examines authentic hadiths from Bukhari, Muslim, and Abu Dawud related to tolerance. Three case studies are analyzed: religious tolerance in Manado, Muslim-Hindu harmony in Bali, and challenges of discrimination against Ahmadiyya. The findings reveal that prophetic hadiths provide comprehensive foundations for tolerance, including prohibition of religious coercion, protection of dhimmi rights, and the concept of wasathiyyah (moderation). Implementation in Manado and Bali demonstrates successful application of hadith values within Indonesia's pluralistic context. However, the Ahmadiyya case indicates challenges in practical implementation. This research concludes that deep understanding of tolerance-related hadiths can serve as a solution to strengthen social harmony and address intolerance in Indonesia's diverse society.